2016
DOI: 10.1038/nmicrobiol.2016.142
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of non-human primates from advanced Sudan ebolavirus infection with lipid encapsulated siRNA

Abstract: Although significant progress has been made in developing therapeutics against Zaire ebolavirus, these therapies do not protect against other Ebola species such as Sudan ebolavirus (SUDV). Here, we describe an RNA interference therapeutic comprising siRNA targeting the SUDV VP35 gene encapsulated in lipid nanoparticle (LNP) technology with increased potency beyond formulations used in TKM-Ebola clinical trials. Twenty-five rhesus monkeys were challenged with a lethal dose of SUDV. Twenty animals received siRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 49 publications
3
49
0
Order By: Relevance
“…Similar observations have been made in animals infected with Sudan virus that were treated with siRNA-LNP 5 days p.i. (6) and also reflect findings in the TKM-Ebola-Guinea phase II clinical trial, which suggested that high viral loads and existing organ injury in subjects probably obscured the ability to detect treatment benefit (7). In the surviving treated animals, viral RNA was detected in most of the tissues assayed, such as the axillary and inguinal lymph nodes and spleen (Figure 2, E and F).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similar observations have been made in animals infected with Sudan virus that were treated with siRNA-LNP 5 days p.i. (6) and also reflect findings in the TKM-Ebola-Guinea phase II clinical trial, which suggested that high viral loads and existing organ injury in subjects probably obscured the ability to detect treatment benefit (7). In the surviving treated animals, viral RNA was detected in most of the tissues assayed, such as the axillary and inguinal lymph nodes and spleen (Figure 2, E and F).…”
Section: Discussionmentioning
confidence: 88%
“…A significant barrier to in vivo application of RNAi has been the development of efficient delivery vehicles that promote cellular uptake (3); however, use of a lipid nanoparticle (LNP) platform not only protects siRNAs from nuclease degradation in the bloodstream but also mediates effective delivery to hepatocytes, a major replication cell for MARV and RAVV. This technology has been used successfully to protect nonhuman primates (NHPs) against EBOV when given before or at the onset of illness (4,5) and against Sudan virus (SUDV, species Sudan ebolavirus) when given at the late stage of disease (6). Although anti-EBOV siRNA-LNP was recently tested in a very small phase II clinical trial, in which it appeared safe but did not show clear benefit, the extremely high viral loads (>9 log 10 copies/ml for all 12 cases) and existing organ injury in the enrolled end-stage patients probably obscured this trial's ability to detect statistically significant treatment efficacy (7).…”
Section: Introductionmentioning
confidence: 99%
“…Their possible role as reservoirs needs to be assessed, especially in Primates, where important zoonotic virus species have been recorded worldwide [e.g. Ebola virus , Marburg virus , Herpes B virus and Hepatitis virus ] (Huff and Peter, ; Bermejo et al, ; Swanepoel et al, ; Thi et al, ; de Carvalho‐Dominguez‐Sousa et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Of the five ebolaviruses known to infect humans, EBOV, SUDV, and BDBV have caused outbreaks with case-fatality rates up to 90% in the last decade (Burk et al, 2016). Although several therapeutic products are in clinical development for the treatment of Ebola virus disease (EVD), no medical countermeasures to SUDV or BDBV have progressed beyond proof-of-concept studies (Corti et al, 2016; Mire et al, 2013; Pascal et al, 2018; Qiu et al, 2014; Thi et al., 2016). To address this unmet public health need, we developed a two-antibody cocktail, MBP134 AF , with demonstrable activity against all known ebolaviruses ( companion report, Wec et al ), including the “pre-emergent” agent Bombali virus recently discovered in molossid bats in Sierra Leone (Goldstein et al, 2018).…”
Section: Introductionmentioning
confidence: 99%